Environmental justice implications of land grabbing for industrial agriculture and forestry in Argentina. Issue 3 (23rd February 2020) - Busscher, Nienke; Parra, Constanza; Vanclay, Frank
Abstract: Land grabbing results in social impacts, injustice, conflict and displacement of smallholders. We use an environmental justice framework to analyse land grabbing and actions taken by local communities (resistance, protest, and proactive organisation). Qualitative research investigating land grabbing for tree plantations and agriculture (primarily soy) was undertaken in Argentina. We found that pre-existing local vulnerabilities tended to result in people acquiescing rather than resisting land grabs. Local people considered existing injustices to be more pressing than land grabbing. Locals tacitly accepted injustice resulting in communities becoming displaced, fenced-in, or evicted. Consequently, already-vulnerable people continue to live in unhealthy conditions, insecure tenure situations, and bear a disproportionate social and environmental burden. More attention should be given to pre-existing vulnerabilities and to improving the wellbeing of people affected by land grabs. Analysing land grabbing from an environmental justice perspective contributes to understanding the deeper reasons about why, where and how land grabbing occurs.